2013
DOI: 10.1007/s00015-013-0120-1
|View full text |Cite
|
Sign up to set email alerts
|

Tectonometamorphic history of the Gruf complex (Central Alps): exhumation of a granulite–migmatite complex with the Bergell pluton

Abstract: We describe field occurrences of sapphirinebearing granulites, charnockites and migmatites in the Gruf complex, Central Alps and present a new geological map and a structural analysis of the entire Gruf complex for the first time. We have carried out an accurate analysis of the relationships between granulite facies metamorphism, migmatisation and deformation within the complex, in relation to the intrusion of the Bergell pluton. Granulites and charnockites display fabrics different from those defined by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…These conditions are well beyond the wet granite solidus and close to fluid-absent muscovite melting (after Vielzeuf and Schmidt 2001 containing granulites, and subordinate metamorphosed ultramafic, basic and rarely carbonate lenses within the migmatitic gneisses (e.g. Galli et al 2012). Previously known only as loose blocks (Cornelius 1916;Wenk et al 1974), we have documented the outcrops of sapphirineopx granulites, as rare schlieren within charnockites and as relict enclaves in migmatitic orthogneisses and charnockites (Galli et al 2011).…”
Section: Geological Settingmentioning
confidence: 95%
See 2 more Smart Citations
“…These conditions are well beyond the wet granite solidus and close to fluid-absent muscovite melting (after Vielzeuf and Schmidt 2001 containing granulites, and subordinate metamorphosed ultramafic, basic and rarely carbonate lenses within the migmatitic gneisses (e.g. Galli et al 2012). Previously known only as loose blocks (Cornelius 1916;Wenk et al 1974), we have documented the outcrops of sapphirineopx granulites, as rare schlieren within charnockites and as relict enclaves in migmatitic orthogneisses and charnockites (Galli et al 2011).…”
Section: Geological Settingmentioning
confidence: 95%
“…These granulites are typically composed of 60-80% mafic minerals (sapphirine, opx, garnet, Ti-rich biotite; Wenk et al 1974) and are interpreted as the refractory residue after extraction of considerable amounts of charnockitic melt from a Mg-Al-rich metapelitic precursor (Galli et al 2011). While the granulite peak conditions are extreme at crustal levels and do not fit any known metamorphic event in the Central Alps, post-peak conditions of 720-740°C leading to partial melting match the generally accepted mid-Tertiary regional metamorphic conditions for this part of the Alps (Bucher-Nurminen and Droop 1983; Burri et al 2005;Galli et al 2012). This duality renders the UHT metamorphism a questionable Alpine event.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bergell intrusion depth was estimated at about 22-26 km on the basis of Al-in-hornblende barometry, which yielded 0.62 ± 0.05 GPa for samples close to Bivacco Marinetti in the upper Codera valley (Davidson et al 1996, Reusser 1987, which is the same COD locality where most our pegmatite and mylonite samples come from. Migmatization in the Gruf complex host rocks was coeval with the emplacement of the Bergell batholith and was estimated by Galli (2013) to occur at 0.6-0.7 GPa and 700-750 °C (to as much as 750-755 °C close to the pluton contact). These ambient conditions clearly exceeded the conditions of pegmatite intrusion.…”
Section: Pressure-temperature Conditions Of the Host Rocks During Pegmentioning
confidence: 99%
“…He also reported mutual crosscutting relationships between pegmatites and the Novate intrusion, from which he inferred that they were broadly contemporaneous. Galli et al (2013) reported that aplite and pegmatite dikes are present within (and show a weaker ductile overprint than) mylonites (their Fig. 13e), indicating that the emplacement of these dikes was late, but still syntectonic.…”
Section: Introductionmentioning
confidence: 97%